(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The synthesis mediated by water has become a revolutionary approach in contemporary organic chemistry, providing an eco-friendly substitute for traditional reactions that utilize organic solvents.Consistent with the tenets of green chemistry, water is an excellent medium for reactions because of its non-toxic nature, plentiful availability, affordability, and distinctive physicochemical characteristics, such as high polarity, the ability to form hydrogen bonds, and the hydrophobic effect. Water as solvent the unique properties of water enhance reaction rates, improve selectivity, simplify product isolation, and reduce waste and energy consumption. This review explores the principles of water-mediated synthesis, its role in organic transformations, and its advantages over conventional solvents. It also highlights applications in pharmaceutical synthesis, nanotechnology, polymer chemistry, and biocatalysis, emphasizing the increasing industrial importance of aqueous synthetic methods. Recent advance Emerging approaches such as micellar catalysis, nanoparticle-assisted reactions, microwave- and ultrasound-assisted synthesis, and continuous-flow processes expand the scope of water-mediated chemistry. Despite challenges like poor solubility of hydrophobic substrates and moisture-sensitive reagents, advances in catalysis and reaction engineering continue to address these limitations. Conclusion Water-mediated synthesis provides a sustainable and efficient platform for modern chemical transformations, enabling cleaner and safer processes. Continued advances in catalyst design, process optimization, and industrial-scale implementation are expected to further establish water as a key green reaction medium in organic synthesis.